World kidney day 2018; chronic kidney disease in women - Mehrdad Zahmatkesh; Mohammad Reza Tamadon (Society of Diabetic Nephropathy Prevention, 2018)
Context: Chronic kidney disease (CKD) is a worldwide public health problem and its occurrence and prevalence are on the rise. One of the populations with an increase in the occurrence of CKD is women. .In this study we reviewed previous studies in order to investigate main concern in women with CKD. Evidence Acquisition: PubMed, EBSCO, Embase Web of Science, directory of open access journals (DOAJ), Scopus, and Google Scholar have been searched. Results: Main concerns in women with CKD are including menstruation irregularity and dysfunction, decreased sexual desire, high-risk pregnancy, prenatal and fetal complications, early menopause and vitamin D deficiency. Conclusions: Women need to special attention due to some physical and physiological differences such as hormonal difference, menstruation period, pregnancy and menopause. Patient's education and awareness of health care personnel are very effective in achieving the goals.